SKELETAL REMAINS AND DEATH RITUAL ANALYSIS OF ANCIENT BURIALS IN LATEA CAVES, TENTENA VILLAGE, INDONESIA - Ni Gusti Ayu Putu Intan Kumbayoni; Hendra Hendra (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Tentena Village in Poso Regency, Central Sulawesi, Indonesia features several caves with ancient burials. These burials have been confirmed as cultural heritage sites under the protection of the Indonesian government laws number 10 of 2010 about cultural heritages; however, there is minimal knowledge about the history and the religious significance of the burials that have been documented. Within the current literature, there has been no systematic research conducted on the historical and cultural aspects of the human remains in these caves. The lacks of information makes the generation of the community where the sites belong feel that there is no bond between them and the sites. This problem triggers indifferent attitude toward sites preservation. As a response to this gap within the literature, this study aims to observe and analyze the historical aspects specified in the death rituals focused on the Latea Caves’ burial site through identifying the skeletal remains. The method that was applied in this research is a mix-method approach. The quantitative method is used to collect the statistical data on the remains and artifacts based on the forensic anthropological examination techniques and DNA analysis while the qualitative method is used to obtain data from in-depth interviews and focus group discussions with the Pamona ethnic group. The decision to conduct interviews with this group is due to the skeletons likely belonging to the ancient Pamona tribe from Wawolembo Hill, which fought with the Napu tribe during a tribal war in approximately 1400 BC. Application of basic forensic anthropology identification techniques and DNA analysis found that the majority of the skeletal remains are composed of women. These results are significant in providing information about the burial practices and the indigenous culture of the Pamona ethnic group.